PERANCANGAN UI/UX APLIKASI PET CARE UNTUK PELANGGAN MENGGUNAKAN METODE DESIGN THINKING - Amalia Rodhya Ulfa; Abdul Rezha Efrat Naja; Prasasti Karunia F.A (CV. Adiba Aisha Amira, 2026)
Pets play an important role in human life, yet owners often face difficulties in accessing complete and efficient pet care services. This study aims to design a mobile-based pet care application with a focus on user experience (UI/UX) using the Design Thinking method. The research process involves the stages of empathize, define, ideate, prototype, and test. Data were collected through interviews with 5 customers and 15 pet care owners and analyzed using empathy maps, user personas, and wireflows. The prototype was tested using the System Usability Scale (SUS) to assess usability and user comfort. The SUS test results showed an average score of 73.5, categorized as good and acceptable, indicating that the application has good usability. This study demonstrates that proper UI/UX design can enhance accessibility, efficiency, and user satisfaction in pet care services.